PEMBERONTAKAN PRRI SUMATERA SELATAN TANPA DEWAN GARUDA - Apriansyah, Diki Tri; Wargadalem, Farida Ratu (Universitas Negeri Malang, 2020)
Abstract: PRRI South Sumatra is part of the central PRRI. Initially, Barlian (Garuda Council) along with other leaders in Sumatra played a crucial role in demanding the central government to pay more attention to the regions. However, Barlian withdrew in the midst of its development, when it changed to insistence on the central government, until it become a PRRI rebellion. Under the leadership of Nawawi, PRRI South Sumatra rebellion extended until Bengkulu and MUBA. The purpose of this paper is to define how Barlian's attitude shifted to